Characterization of South African adolescents with alcohol use disorders but without psychiatric or polysubstance comorbidity - Ferrett, Helen L. (2011)
BACKGROUND: Individuals who begin drinking during early adolescence and exhibit externalizing pathology and disinhibitory/dysregulatory tendencies are more vulnerable to developing alcohol use disorders (AUD) in adulthood. Previous research has focused on in-treatment populations with substantial comorbid psychopathology and polysubstance use. Here we characterize a unique sample of treatment-naïve adolescents without such comorbidity to help identify vulnerable youth who may benefit from early intervention. METHODS: We compared externalizing propensity, disinhibitory characteristics, and school performance in adolescents with AUD (but without comorbid psychopathology or other substance use; n=70) to those of demographically matched controls (n=70). Within the AUD group, we compared measures of substance use and the disinhibitory syndrome between males and females with differing severity of externalizing propensity. RESULTS: Adolescents with AUD demonstrated more externalizing propensity and disinhibitory personality traits (impulsivity, novelty seeking and excitement seeking), poorer self-monitoring and response inhibition, more bullying and sexual risk-taking behavior, poorer first language performance, and greater use of alcohol, cannabis, and nicotine (p <.05). Within the AUD group, participants with higher externalizing propensity began drinking earlier, more frequently, and for a longer duration than those with lower externalizing symptoms (p<.05). Disinhibitory features (personality, cognition and behavior) were, however, not stronger in those with higher externalizing propensity. CONCLUSIONS: We suggest that the constructs of externalizing propensity and disinhibitory syndrome are useful in characterizing treatment-naïve adolescents with AUD but without comorbid psychopathology or polysubstance use. These results support the importance of these constructs in understanding adolescent AUDs, even when the frank externalizing diagnoses of childhood (ODD and CD) are excluded.